Academic Press library in signal processing, Volume 7, Array, radar and communications engineering - Chellappa, Rama; Theodoridis, Sergios 1951- (Academic Press, 2018)
Academic Press Library in Signal Processing, Volume 7: Array, Radar and Communications Engineering is aimed at university researchers, post graduate students and R&D engineers in the industry, providing a tutorial-based, comprehensive review of key topics and technologies of research in Array and Radar Processing, Communications Engineering and Machine Learning. Users will find the book to be an invaluable starting point to their research and initiatives. With this reference, readers will quickly grasp an unfamiliar area of research, understand the underlying principles of a topic, learn how a topic relates to other areas, and learn of research issues yet to be resolved
Keywords: TECHNOLOGY & ENGINEERING / Mechanical; Signal processing